Beyond Biology: The Personality Underpinnings of Chronic Pain - Goli, Farzad (Journal of Personality and Psychosomatic Research (JPPR), 2024)
The factors contributing to chronic pain extends far beyond its physiological underpinnings, weaving through the psychological and personality-based aspects of individuals experiencing such conditions. This letter aims to highlight the critical role personality traits play in both the perception and management of chronic pain, urging a multidisciplinary approach to treatment that encompasses the psychological dimensions of this pervasive issue. The evidence points to a compelling need for a paradigm shift in how we approach chronic pain management. A more holistic model that integrates the psychological and personality-based dimensions of pain alongside traditional biomedical approaches is paramount. Such a model would not only improve our understanding of chronic pain but also enhance the efficacy of treatment interventions by tailoring them to the individual's psychological profile. In conclusion, the intersection of personality and chronic pain represents a fertile ground for future research and clinical innovation. By embracing a more nuanced understanding of pain that incorporates the psychological fabric of the individual, we can move towards more compassionate, comprehensive, and effective treatment strategies.